Fitness Costs Predict Emotional, Moral, and Attitudinal Inbreeding Aversion - Lespiau, Florence; Kaminski, Gwenaël (Frontiers in Psychology, 2016)
In terms of sexual intercourse, the very last people we think about are our kin. Imagining inbreeding intercourse, whether it involves our closest kin or not, induces aversion in most people who invoke inbreeding depression problems or cultural considerations. Research has focused on the disgust felt when facing inbreeding intercourse between close kin but little is known about other responses. In this study, we considered the influence of fitness costs on aversive reactions by including disgust and emotional reaction as well as moral judgment and attitudes towards inbreeding: higher costs should induce a stronger aversive reaction. The fitness costs were manipulated by two factors: (i) the degree of the participants’ involvement in the story (themselves, a sib or an unknown individual), and (ii) the degree of relatedness between the two inbreeding people (brother/sister, uncle-aunt/niece-nephew, cousin). To test this hypothesis, 140 women read and assessed different inbreeding stories varying in the fitness costs incurred. Findings showed that the higher the fitness costs were, the greater the aversive reaction was in an overall way. First, our results fitted with previous studies that tested the influence of fitness costs on disgust. Second, and more interestingly, findings went further by examining overall aversion, showing that fitness costs could influence emotions felt as well as attitudes and behaviors towards inbreeding people. The higher the fitness costs were, the less inbreeding people were perceived as moral and the more they were considered as a nuisance. However, results regarding avoidance were more nuanced.